OPENING THE BLACK BOX OF TECHNOLOGY ADOPTION: THE MOTIVE-TECHNOLOGY-BELIEF FRAMEWORK - ZENOBIA, BRENT A.; WEBER, CHARLES M. (International Journal of Innovation and Technology Management (IJITM), 2011)
A qualitative empirical study explores the psychological process by which transportation consumers adopt alternatives to single occupancy vehicles. The study's findings give rise to the Motive-Technology-Belief (MTB) framework, a theory that conceives of technology adoption in terms of three mental structures: motives are inner mental reasons; technologies are tools that pertain to motives; and beliefs are associations between motives and/or technologies. Their behavioral interactions are governed by three conscious processes: selecting is the process of choosing a tool in response to an immediate need; evaluating is the process of forming beliefs about tools; and maintaining is the process of determining the functional status of tools. They are augmented by five unconscious auxiliary processes: perceiving, focusing, framing, consolidating, and acting. The primary contribution of this paper is the first coherent theory that explains some of the inner mental processes pertaining to technology adoption. However, the study described in this paper also combines existing theory with original field research to lay the foundation for a more comprehensive causal theory of the adoption process that will provide a step-by-step explanation of how events or life experiences cause a consumer's beliefs about a technology to change over time. Finally, the study identifies evaluating, selecting, maintaining, and the auxiliary processes that govern motivation as fundamental "microlaws" of innovation i.e. regular rules describing the generating processes of emergent innovations.